(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics, paraclinical features, and selected related factors among full-term primiparous women indicated for cesarean section at Hai Duong Obstetrics Hospital. Research subjects and methods: A prospective cross-sectional descriptive study was conducted on 235 full-term primiparous pregnant women admitted to the hospital, of whom 137 women had indications for cesarean section at Hai Duong Obstetrics Hospital from October 1, 2024 to December 31, 2024. Results: Women aged 20–30 years accounted for the majority (79.2%). Most participants were self-employed (41.7%) or factory workers (30.6%), lived in urban areas (76.3%), and had a height greater than 150 cm (85.5%). The cesarean section rate among primiparous women was 58.3%. The main reason for hospital admission was abdominal pain (74.5%). Most women presented with cervical dilatation ≤ 2 cm (91.2%), infrequent uterine contractions (92.7%), normal amniotic fluid volume (90.5%), intact membranes (89.0%), normal placental position (99.3%), fetal heart rate of 120–160 beats per minute (95.6%), and neonatal birth weight ranging from 2500 to 3499 g (66.4%). Cesarean section due to two or more indications accounted for 19%, mainly related to fetal and fetal adnexal factors (84.0%). Women with a height of 145–150 cm had a significantly higher rate of cesarean section compared with vaginal delivery. Conclusion: The rate of cesarean section among first-time mothers was relatively high, mainly due to fetal and placental factors. Maternal height was significantly associated with the indication for cesarean section.